Fuzzy Controller Parameters Optimization Based Particle Swarm Optimization Algorithm for Electro-Hydraulic System - Majeed Abdullah, Zaki (Anbar Journal of Engineering Sciences, 2017)
Particle Swarm Optimization Algorithm (PSOA) has emerged recently as an efficient and powerful technique for the optimization of real parameters. The current study presents control scheme for electro-hydraulic actuator system which utilizes particle swarm optimization (PSO) for off-line tuning of the Fuzzy Proportional-Derivative (Fuzzy PD) controller. The gains and Membership Functions (MFs) tuned by PSOA which has been implemented depending on the performance indices: ITAE (Integral Time of Absolute Error), ISE (Integral Square of Error), and IAE (Integral Absolute of Error).